LANGUAGE TEST TAKING IN ALBANIAN SCHOOLS CASE OF THE ENGLISH LANGUAGE - Alimemaj, Zamira (PEOPLE: International Journal of Social Sciences, 2015)
Test taking is often very stressful and frustrating for students .Experts tend to focus more on the kinds of tests that work best for students and overlook the emotional aspect of the matter. One of the most important things in successful test taking is exactly the ability of students to cope with the situation. We will provide an overview of test types mostly used by teachers and see how successful and efficient they are. We will first attempt to draw a definition of test taking in order to have a starting point for our discussion. The regular assessment of students’ progress is an inseparable part of the teaching and learning process. It is a type of information necessary for students grading and for providing evidence of teaching and learning effectiveness. This assessment takes various forms as there are many procedures and techniques followed by teachers to evaluate them. In this process test taking is an essential part.